Accuracy of Hemoglobin E Screening Test Using Allelic Discrimination Assay - Supranee Upanan; Somdet Srichairatanakool; Sirivipa Piyamongkol; Wirawit Piyamongkol (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To determine the accuracy of allelic discrimination (AD) assay for hemoglobin E (Hb E) screening test in Chiang Mai Strategy for thalassemia prevention and control. Materials and Methods: This study evaluated the AD assay compared with conventional Hb E screening tests used in Chiang Mai Strategy of Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. In this assay, two TaqMan probes were designed to discriminate heterozygous and homozygous by detecting normal and mutant nucleotides of Hb E gene. Results: From 55 blinded DNA samples, the AD assay revealed the results with 100% sensitivity, specificity, positive predictive value, negative predictive value and efficiency when compared to the conventional Hb E screening tests of the Chiang Mai Strategy. Conclusion: The AD assay is effective as an Hb E screening test in the thalassaemia prevention and control program. Moreover, AD assay can distinguish heterozygous from homozygous genotypes.